2002
DOI: 10.1093/milmed/167.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Racial Variations in Department of Veterans Affairs Ambulatory Care Use and Unmet Health Care Needs

Abstract: Our objective was to describe racial/ethnic variations in Department of Veterans Affairs (VA) ambulatory care use and its association with the presence of unmet health care needs. Using the 1992 National Survey of Veterans, we examined race/ethnicity and unmet health care need for ambulatory care users of VA and non-VA facilities. Black and Hispanic veterans were more likely to report any VA use. In unadjusted analyses, American Indian/Eskimo, Hispanic, and black veterans were 4.4, 2.5, and 1.9 times more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…One study identified a cycle of passivity in which African American patients, and patients interacting with race discordant physicians, received less information overall because they engaged less often in communication behaviors (e.g., questions, assertions) that typically elicit more information from doctors. 48 In focus groups, African-American patients placed greater emphasis on the need for trust in their physicians in deciding about invasive procedures, whereas white patients placed greater emphasis on clinical indications. 49 Whereas racial differences were apparent in factors that might influence the use of cardiac care-e.g., aversion to surgery, trust, communication-studies that were able to examine the influence of these factors on the actual use of invasive procedures generally found that they did not explain observed disparities.…”
Section: Resultsmentioning
confidence: 99%
“…One study identified a cycle of passivity in which African American patients, and patients interacting with race discordant physicians, received less information overall because they engaged less often in communication behaviors (e.g., questions, assertions) that typically elicit more information from doctors. 48 In focus groups, African-American patients placed greater emphasis on the need for trust in their physicians in deciding about invasive procedures, whereas white patients placed greater emphasis on clinical indications. 49 Whereas racial differences were apparent in factors that might influence the use of cardiac care-e.g., aversion to surgery, trust, communication-studies that were able to examine the influence of these factors on the actual use of invasive procedures generally found that they did not explain observed disparities.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Indeed, the IOM asserts that access-related factors may be the most significant barriers to equitable care, and they must be addressed as an important first step toward eliminating health care disparities. 10 …”
Section: Financial Aspects Of Healthcare Delivery Rationalementioning
confidence: 99%
“…[1][2][3][4][5] Examples include disparities in receipt of surgical procedures, cancer care, intensity of hospital services, and treatment of pain. 2,3,[6][7][8][9] The Institute of Medicine (IOM) defines disparities in health care as racial or ethnic differences in the quality of health care that are not caused by differences in clinical need, patient preferences, or appropriateness of intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations associated with race or ethnicity may stem from differences in biology (132), behavior (94), and/or exposure to environmental factors (117). Similarly, variations in health outcomes have been linked to biologic determinants, social determinants, (5,121) and their interaction (53). Although race or ethnicity, per se, is not causal, it may still function as a risk indicator providing some reduction in uncertainty about the likelihood of morbidity or mortality (105).…”
Section: As a Risk Indicator For Health Outcomesmentioning
confidence: 99%